Holistic Nursing Care in Improving Patient Safety - Indrayadi Indrayadi; Rahmat Pannyiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Patient safety is a key indicator of healthcare quality. One approach that can improve patient safety is the implementation of holistic nursing care, encompassing the biological, psychological, social, and spiritual aspects of the patient. This approach enables nurses to provide comprehensive, patient-centered care. This study aims to determine the relationship between holistic nursing care and improved patient safety. This study used quantitative methods with an analytical design and a cross-sectional approach. Sectional. The research sample was nurses in health care facility X. Data were collected using a questionnaire and analyzed using the Chi- Square test. The results showed that the implementation of holistic nursing care was significantly related to increased patient safety (p < 0.05). The conclusion of this study is that holistic nursing care plays an important role in improving patient safety.